Status of Dental Caries and Oral Health Behaviour among 6 to 9 Years Children Attending at a Dental College Hospital in Dhaka City - Alam, Md. Shafiul; Shahed, Abu Mohammad; Mesbah, Fahmida Binte; Haque, Mohammad Ahtashamul; Azam, Md. Shafiul; Mian, Md. Anowar Hussain (Journal of National Institute of Neurosciences Bangladesh, 2025)
Background: Oral hygiene is the method that is used to `prevent pathological condition that affect mouth like gum disease, cavities, mouth sores and ulcers. Objective: The purpose of this study was to observe oral health behavior among the children of 6 to 9 years’ old such as regular tooth brushing, uses of oral hygiene aids and dental attendance to maintain their good oral health for a life time. Methodology: This cross-sectional study conducted in Dhaka Dental College and Hospital, Bangladesh study was carried out from October 2019 to September 2020. A total of 175 participants’ children aged 6 to 9 years attending at the OPD with dental Caries in Dhaka Dental College Hospital were the study population. The study population were included children aged 6 to 9 years in Dhaka dental college and hospital who were available and wished to participate. The questionnaire was used in this study pre-tested before the data collection, data was collected using semi-structured questionnaire by face-to-face interview. Results: A total of 175 children were examined during the study. Among them 65.13% were suffering from caries teeth. Among the majority of children (40.57%) dental caries was from government primary school as compare from private primary school (15.43%). The dmft score of 1 or higher increases with the increasing age of the children. 7 to 8 years’ children (20.57%) had high dmft score. High DMFT score indicates significant relation between age of children and dmft scores (P=.000, <0.01). Among them 66.86% children brush their teeth regularly whereas 33.14% followed irregularly brush their teeth and only 20.4% brush their teeth twice daily which are recommended whereas majority 79.6% brush their teeth once daily. Among them had habit of snacking aftermeal observed in 87.43% of the participants but only 15.43% of children cleaned their teeth after snack food. Conclusion: Good oral health behavior plays a fundamental role for general wellbeing by preventing common oral diseases, such as dental caries and periodontal disease, especially in children who live in developing countries. Journal of National Institute of Neurosciences Bangladesh, January 2024;10(1):38-43